2013
DOI: 10.3892/etm.2013.1158
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the therapeutic effects of various methods for the treatment of chronic atrial fibrillation

Abstract: The aim of this study was to analyze the therapeutic effects of various methods for the treatment of chronic atrial fibrillation (AF). Randomized controlled trials (RCT) concerning drug therapy and catheter ablation for the treatment of chronic AF were retrieved. The RevMan 5.1 software package was used for the meta-analysis. A total of 20 papers were assessed in this study. The results of the analysis indicated that the success rate was lower [odds ratio (OR), 8.94; 95% confidence interval (CI), 4.70–17.02; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia reported in clinical practice (1). There are three predominant mechanisms underlying AF: Electrical remodeling, structural remodeling and autonomic nerve remodeling (2).…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia reported in clinical practice (1). There are three predominant mechanisms underlying AF: Electrical remodeling, structural remodeling and autonomic nerve remodeling (2).…”
Section: Introductionmentioning
confidence: 99%
“…Success rates were lower in persistent or permanent AF patients (Lin et al . ). Incomplete or non‐transmural isolation may lead to AF recurrence and require another intervention.…”
Section: Introductionmentioning
confidence: 97%